KESIAPAN MENTAL ATLET PUTRI HOCKEY LAMPUNG PADA KEJURNAS HOCKEY INDOOR U-21 TAHUN 2025 - Cholid, Icha; Wicaksono, Lungit; Jaya Sumantri, Riyan; Siswoyo, Joan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mental preparedness is an important aspect that helps athletes face the pressures and demands of competition. This study aims to analyze the mental preparedness of female hockey athletes from Lampung and the factors influencing their competition anxiety in facing the 2025 U-21 National Indoor Hockey Championship. This research applied a descriptive qualitative case study method. The informants consisted of one coach, twelve female athletes, and two parents of athletes selected through purposive sampling. Data were collected through observation, interviews before and after matches, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing. The findings show that athletes’ mental readiness is reflected in achievement motivation, self-confidence, maintaining focus and concentration, emotional management, fighting spirit, and competition experience, which help athletes face the pressure of a national championship. However, in high-pressure match situations, especially final matches, some athletes still experience nervousness, fear of making mistakes, and difficulty maintaining focus and controlling emotions. Competition anxiety is related to intrinsic and extrinsic factors. Intrinsic factors include competitive motivation, self-confidence, focus and concentration, emotional regulation and coping, competition experience, and mental toughness. Extrinsic factors include the coach’s role, support from parents and family, teammate support and team cohesion, the competition environment and venue, training facilities, and organizational support. The study concludes that athletes’ mental readiness is an interaction between intrinsic and extrinsic factors that are closely interconnected with competition anxiety in facing a championship.